2011 21st International Conference on Field Programmable Logic and Applications 2011
DOI: 10.1109/fpl.2011.102
|View full text |Cite
|
Sign up to set email alerts
|

Improved Abstractions and Turnaround Time for FPGA Design Validation and Debug

Abstract: Design validation is the most time-consuming task in the FPGA design cycle. Although manufacturers and third-party vendors offer a range of tools that provide different perspectives of a design, many require that the design be fully re-implemented for even simple parameter modifications or do not allow the design to be run at full speed. Designs are typically first modeled using a high-level language then later rewritten in a hardware description language, first for simulation and then later modified for synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Scan techniques can provide complete visibility into the state of all flip-flops in the design but typically require that the circuit be halted before scan-out. This can greatly slow down their use for real-time debugging; Iskander et al [2011] reported that viewing one flip-flop using device readback can take 2-8 seconds.…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…Scan techniques can provide complete visibility into the state of all flip-flops in the design but typically require that the circuit be halted before scan-out. This can greatly slow down their use for real-time debugging; Iskander et al [2011] reported that viewing one flip-flop using device readback can take 2-8 seconds.…”
Section: Related Workmentioning
confidence: 98%
“…Scan-based techniques involve connecting internal flip-flops sequentially; in FPGAs, this can be achieved using general-purpose soft-logic, as in Wheeler et al [2001], where the area and delay costs can be prohibitive, or through dedicated device readback support [Iskander et al 2011]. Scan techniques can provide complete visibility into the state of all flip-flops in the design but typically require that the circuit be halted before scan-out.…”
Section: Related Workmentioning
confidence: 99%
“…In this work they do not use trace buffers, but rather leverage the device readback feature of certain FPGAs, that allows all registers within the FPGA to be read externally. The major drawbacks of this approach is that it is very slow, requiring several seconds to read values from the FPGA [30], and that it can only be used for a live-stepping flow. In order to perform in-situ debugging, the circuit would need to be started and stopped for each instruction.…”
Section: Related Workmentioning
confidence: 99%
“…Typically it involves selecting a large number of signals, tracing their values concurrently during the execution, and analyzing them to find misbehaviors. To effectively do this, any HW debugging technique needs to provide three main features [2]: 1) signal observability; 2) hardware controllability; 3) limited turnaround times. Signal observability is the ability to see the values of the largest number of signals in the design, with the finest granularity, across the largest time span as possible.…”
Section: A Approaches and Challenges In Hardware Debuggingmentioning
confidence: 99%